Rehabilitation of a young athlete with extension-based low back pain addressing motor-control impairments and central sensitization - Winslow, J. J.; Jackson, M.; Getzin, A.; Costello, M. (Journal of Athletic Training, 2018)
Objective: To describe the conservative management of a young athlete with extension-based (EB) low back pain (LBP).